Political Hoaxes in the Post-Truth Era: An Islamic Political Analysis - Agustina, Isna Fitria; Ali, Zezen Zainul; Sakirman, Sakirman; Octavianne, Helena; Jamal, Muhammad (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This study aims to examine how the phenomenon of political hoaxes in the post-truth era occurs and what impact it has on the religious life and political direction of the Muslim community. This research departs from the phenomenon of political hoaxes that are getting stronger, especially when approaching election contestation. This condition is reinforced by the post-truth era where the truth is no longer urgent and trusted because the many hoaxes circulating make hoaxes like the truth. This research is a literature study explaining the phenomenon of political hoaxes in the post-truth era with an Islamic political sociology approach, data obtained from literature related to hoax politics, the post-truth era and analyzed in depth. The findings of this study are: First, the phenomenon of political hoaxes is carried out massively and repeatedly, especially before political events, Second, the reinforcing factors of political hoaxes in Muslim societies are caused by identity politics and low digital political literacy that are spread repeatedly. Third, political hoaxes can trigger inter-religious conflicts including intolerance and radicalism, disrupt religious life, and increase polarization and distrust of political institutions, as well as distrust of the media. Fourth, overcoming the impact of political hoaxes can be done by taking an Islamic political approach in society, namely by always telling the truth and bertabayyun against news and increasing digital literacy and the role of religious authorities.